RETRACTED ARTICLE: Repression of lncRNA-SVUGP2 mediated by EZH2 contributes to the development of non-small cell lung cancer via brisking Wnt/β-catenin signal - Sen Wei; Jinghao Liu; Xin Li; Xingyu Liu (Artificial Cells, Nanomedicine, and Biotechnology)
We, the Editors and Publisher of the journal Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article:Sen Wei, Jinghao Liu, Xin Li & Xingyu Liu (2019) Repression of lncRNA-SVUGP2 mediated by EZH2 contributes to the development of non-small cell lung cancer via brisking Wnt/β-catenin signal. Artificial Cells, Nanomedicine, and Biotechnology, 47:1, 3400–3409, DOI: 10.1080/21691401.2019.1648279Since publication, the authors repeated some of their experiments and found that under the same conditions they could not repeat the results reported in this paper. As this error directly impacts the reported results and conclusions the authors alerted the issue to the Editor and Publisher and all have agreed to retract the article to ensure correction of the scholarly record.We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions.The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.